Measurement and analysis of flow of concentrated fiber suspensions through a 2‐D sudden expansion using UVP. Issue 3 (9th August 2012) - Claesson, Julia; Rasmuson, Anders; Wiklund, Johan; Wikström, Tomas
<x xml:space="preserve">Abstract</x> The ultrasound velocity profiling technique (UVP) was used to study flow structures after a two‐dimensional (2‐D) 1:11 sudden expansion of pulp fiber suspensions at varied average velocities (1–2.2 m/s) and concentrations (1.8 and 2.8 wt %). One advantage of studying jet geometry is the potential to investigate the main flow structures away from walls. Measurements done at the same percent of the total jet length, at constant concentration, show that an increase in flow rate gave a faster decrease in centerline velocity and a quicker increase in jet width. Increasing the concentration, at the same jet length, the centerline velocity was more stable and the width of the mixing layer increased more rapidly. Comparisons with CFD simulations in the laminar regime, using the Bingham plastic model, show that the main flow structures were captured if the yield stress used in the simulations is approximately 20% of the measured using a rheometer. © 2012 American Institute of Chemical Engineers AIChE J, 59: 1012–1021, 2013